Ocular penetration of topical ciprofloxacin and norfloxacin drops and their effect upon eyelid flora. Issue 7 (July 1994) - Leeming, J P; Diamond, J P; Trigg, R; White, L; Hoh, H B; Easty, D L
Abstract : A double blind, prospective study was undertaken to compare aqueous humour penetration of topical 0.3% norfloxacin and 0.3% ciprofloxacin and their effect upon normal eyelid flora in 39 patients undergoing cataract surgery. Lid swabs were taken before and after six 1 hourly applications of single drops of ciprofloxacin or norfloxacin given before surgery. Aqueous humour was aspirated at surgery and antibiotic concentration assayed using high performance liquid chromatography. The mean aqueous humour concentrations were: ciprofloxacin 220 ng ml-1, norfloxacin 140 ng ml-1. Although this difference was not statistically significant (p = 0.112) the trend demonstrated may be relevant clinically, especially considering the greater activity of ciprofloxacin. Both coagulase negative staphylococcal (p = 0.004) and total bacterial (p = 0.019) lid counts dropped sixfold after ciprofloxacin treatment but the smaller reductions noted after norfloxacin application did not achieve statistical significance (p > 0.1). The reduction of external eye flora experienced with ciprofloxacin suggests that this may be a useful presurgical prophylactic agent.